2019
DOI: 10.1108/jaar-02-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

How IFRS influence the relationship between the types of FDI and economic growth

Abstract: Purpose The purpose of this paper is to examine the relationships between International Financial Reporting Standards (IFRS), types of foreign direct investment (FDI) – greenfield investments (GFIs) and mergers and acquisitions (M&As) – and economic growth in 49 African countries between 2003 and 2017. Design/methodology/approach In the study, panel data fixed effects and generalized method of moments estimation techniques are used in order to test the hypotheses. Findings Using country-level data obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 93 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…, 2019). Akusik Orhan and Mangaliso Mzamo P. also collaborated and presented papers titled “IFRS, FDI, Economic Growth and Human Development: The Experience of Anglophone and Francophone African Countries” and “How IFRS Influence the Relationship between the Types of FDI and Economic Growth: An empirical Analysis on African Countries” (Akisik and Mangaliso, 2020; Akisik et al. , 2020).…”
Section: Bibliometric Analysis and Discussionmentioning
confidence: 99%
“…, 2019). Akusik Orhan and Mangaliso Mzamo P. also collaborated and presented papers titled “IFRS, FDI, Economic Growth and Human Development: The Experience of Anglophone and Francophone African Countries” and “How IFRS Influence the Relationship between the Types of FDI and Economic Growth: An empirical Analysis on African Countries” (Akisik and Mangaliso, 2020; Akisik et al. , 2020).…”
Section: Bibliometric Analysis and Discussionmentioning
confidence: 99%
“…Since the beginning, IFRS were adopted by numerous countries worldwide, which motivated several studies about the determinants of adoption (Alon and Dwyer 2014;Christensen et al 2013;Judge et al 2010;Ramanna and Sletten 2014;Stainbank 2014). Overall, studies indicate that the adoption of IFRS has a positive impact on economic growth in both developed and developing countries (Akisik and Mangaliso 2019;Lungu et al 2017;Oppong and Aga 2019). A study of how IFRS adoption has affected EU economic growth from 2005 to 2014 found a positive and significant relationship between IFRS adoption and economic growth and that full adoption of IFRS has a significant impact on economic growth in both developed and developing countries, in contrast with partial adoption of IFRS that only impacts developing countries economic growth (Oppong and Aga 2019).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…A question of interest is whether the adoption of AAOIFI was beneficial in attracting international firms to the hosted markets for IFIs. The future research can extend this debate into the macro level by measuring the macroeconomics consequences for AAOIFI by testing the effects on foreign direct investments (Akisik and Mangaliso, 2019), economic growth (Oppong and Aga, 2019) and international stock listings (Khan et al , 2020) Several literatures as presented above measure the factors behind AAOIFI compliance. Most of these studies focus mainly on firm features and CG of BOD with scarcity in the impact of macroeconomics factors such as GDP, inflation and education level and religious awareness. Most of the related previous studies emphasize on measuring the AAOIFI disclosure from quantity approach by measuring a dummy variable or based on unweighted checklist index.…”
Section: Recommendations and Directions For Future Researchmentioning
confidence: 99%
“…A question of interest is whether the adoption of AAOIFI was beneficial in attracting international firms to the hosted markets for IFIs. The future research can extend this debate into the macro level by measuring the macroeconomics consequences for AAOIFI by testing the effects on foreign direct investments (Akisik and Mangaliso, 2019), economic growth (Oppong and Aga, 2019) and international stock listings (Khan et al , 2020)…”
Section: Recommendations and Directions For Future Researchmentioning
confidence: 99%